Komunikasi Kepala Sekolah Dalam Meningkatkan Potensi Kinerja Guru Di Madrasah Aliyah Islamiyah Sunggal - Rizka Amanda Putri; Rahmatun Nisa; Muhammad Chaidir; Tengku Darmansah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Principal communication is the process of conveying information to teachers and forwarded to students. The purpose of this study was to determine the principal's communication, including: Teacher professionalism; Teacher discipline; and Teacher responsibility. Qualitative approach with descriptive method. In terms of data collection is through literature study, literature study is the initial step in the data collection method. Literature study is a data collection method that is directed at finding data and information through documents, both written documents, photographs, images, and electronic documents that can support the writing process. The subjects of the study were teachers, principals, and school committees at Madrasah Aliyah Islamiyah Sunggal. The results of the study found: Principal communication in improving teacher professionalism is conveying messages to teachers both verbally and in writing; Principal communication in improving teacher discipline is providing exemplary examples by attending school on time; Principal communication in improving teacher responsibility is interpersonal communication, communication in solving problems in learning by coordinating and finding solutions with the school committee and supervisor, and the relevant Education Office. It is expected that the committee and the principal can provide encouragement and guidance in teacher performance regarding professionalism, discipline and teacher responsibility effectively and efficiently so that it can improve teacher performance in schools.